Mappatura delle coperture in cemento-amianto mediante telerilevamento: review e casi di studio italiani (GEOmedia, 2020)
Asbestos is still a common problem in a lot of country in the word. It was widely used during the 20th century thanks to its numerous physical and mechanical characteristics.Both the European and the Italian legislations have banned the manufacture, importation, processing and distribution in commerce of asbestos-containing products andhave recommended action plans for the mapping and safe removal of asbestos from public and private buildings.The aims of this paper is to elaborate a specific overwiev on the application of remote sensing for mapping the asbestos cement roofs, reporting the Italian experience as acase study, considering different types of sensors, platforms, processing models used for this application.